Low HER2 expression is a predictor of poor prognosis in stage I triple-negative breast cancer - Sanomachi, Tomomi; Okuma, Hitomi Sumiyoshi; Kitadai, Rui; Kawachi, Asuka; Yazaki, Shu; Tokura, Momoko; Arakaki, Motoko; Saito, Ayumi; Kita, Shosuke; Yamamoto, Kasumi; Maejima, Aiko; Kojima, Yuki; et al. (Frontiers in Oncology, 2023)
Introduction Triple-negative breast cancer (TNBC) is negative for hormone receptors and human epidermal growth factor receptor 2 (HER2). In stage I TNBC, adjuvant therapy or follow-up are performed according to risk factors, but clinical trial data is scarce. In recent years, it has been reported that HER2-low cases (1+/2+ and in situ hybridization negative) have different prognoses than HER2-0 cases. However, the risk of recurrence and risk factors in this HER2-low population for stage I TNBC have not yet been investigated. Methods Herein, out of 174 patients with TNBC who underwent surgery from June 2004 to December 2009 at the National Cancer Center Hospital (Tokyo), we retrospectively examined 42 cases diagnosed as T1N0M0 TNBC after excluding those treated with preoperative chemotherapy. Results All patients were female, the median age was 60.5 years, and 11 cases were HER2-low and 31 cases were HER2-0. The median follow-up period was 121 months. Postoperative adjuvant therapy was administered in 30 patients and recurrence occurred in 8 patients. HER2-low cases showed a significantly shorter disease-free survival (HR: 7.0; 95% CI: 1.2– 40.2; P=0.0016) and a trend towards shorter overall survival (hazard ratio [HR]: 4.2, 95% confidence interval [CI]: 0.58–31.4) compared with that of HER2-0 cases. HER2 was also identified as a factor for poor prognosis from the point- estimated values in univariate and multivariate analyses after confirming that there was no correlation between the other factors. Conclusion For patients with stage I TNBC, the HER2-low population had a significantly worse prognosis than the HER2-0 population.